The Role of School Leadership in Enhancing Teacher Professional Competence at SD Negeri 2 Tubanan, Jepara - Endah Soriyawati; Yovitha Yuliejantiningsih; Muhammad Prayito (Journal of Educational Sciences, 2026)
This study aims to analyze the role of school leadership in enhancing the professional competence of teachers at SD Negeri 2 Tubanan, Jepara. The findings indicate that the leadership of the principal significantly contributes to the improvement of teachers' professional competence through effective supervision, motivation, and the provision of continuous professional development opportunities. The principal’s role as a supervisor involves regular classroom visits, providing constructive feedback, and ensuring teachers have the resources and support they need to improve. Furthermore, the principal fosters a collaborative environment by encouraging teachers to participate in relevant training programs, thus enhancing their pedagogical skills. However, challenges such as time constraints for training, the integration of technology in teaching, and the motivation of some teachers to participate in professional development programs remain. This study highlights the importance of principal leadership in promoting professional growth and its direct impact on the overall quality of education. It also offers practical insights for future educational leadership practices.